2022
DOI: 10.1007/s12144-022-02699-7
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance under COVID-19: The role of online learning readiness and emotional competence

Abstract: The COVID-19 pandemic caused school closures and social isolation, which created both learning and emotional challenges for adolescents. Schools worked hard to move classes online, but less attention was paid to whether students were cognitively and emotionally ready to learn effectively in a virtual environment. This study focused on online learning readiness and emotional competence as key constructs to investigate their implications for students’ academic performance during the COVID-19 period. Two groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 116 publications
(130 reference statements)
1
32
0
1
Order By: Relevance
“…Hence, educational institutions face the threat of cyber-attacks that aim to access information related to exams or tamper with students' data and grades. The matter becomes more dangerous when talking about institutions of higher education and scientific research [16], [17]. Statistics indicate that the field of education in particular, the losses resulting from the data breach amounted to about 3.9 million dollars [18], while the losses caused by data breaches in scientific research will cost approximately 1.53 million dollars [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, educational institutions face the threat of cyber-attacks that aim to access information related to exams or tamper with students' data and grades. The matter becomes more dangerous when talking about institutions of higher education and scientific research [16], [17]. Statistics indicate that the field of education in particular, the losses resulting from the data breach amounted to about 3.9 million dollars [18], while the losses caused by data breaches in scientific research will cost approximately 1.53 million dollars [19].…”
Section: Introductionmentioning
confidence: 99%
“…This study also found that, compared with the N to N Group, the ID to ID Group had a lower academic performance ranking, which is consistent with previous research conclusions ( 33 ). By improving students’ online learning readiness and emotional competence during the epidemic, it can help improve their academic performance ( 34 ). In addition, the family function integrity (APGAR scores) of the N to N Group is higher than that of the ID to ID Group, suggesting that the family function integrity is significantly related to the changes in Internet behavior ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Attention was focused mainly on coping with technology and the problems that ensued while using it; for example, unstable internet connections, bandwidth, lack of equipment, inability to rely on communication between students and lecturers and between students and students, slow operation of learning platforms, etc. (Liu et al, 2021;Wang et al, 2022). The second was pedagogy.…”
Section: Introductionmentioning
confidence: 99%